Glycerol in food, cosmetics and pharmaceutical industries: Basics and new applications - Nur Izyan, Wan Azelee; Aizi Nor Mazila, Ramli; Nor Hasmaliana, Abdul Manas; Nurrulhidayah, Salamun; Rohaida, Che Man; El Enshasy, Hesham (IJSTR, 2019)
The world demand for a greener and sustainable environment has driven researchers all over the world to put effort in utilizing all the waste into valuable products. The circular economy is aiming to reduce the amount of waste being produced to almost zero waste by reutilizing and recycling as possible as we can. Glycerol being one of the main by-product from the biodiesel production is recently gaining interest as one of the emerging renewable feedstock for various applications. This mini review starts with a brief introduction on the history and physico-chemical properties of glycerol. The state-of-the-art for different types of glycerol production is also reviewed from the perspective of conventional chemical process as well as biological process. Finally this work highlights the potential of glycerol applications in food, cosmetics and pharmaceutical industries.